2022
DOI: 10.1021/acsestwater.2c00024
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Composite Materials for the Simultaneous Removal of Pharmaceuticals, Personal Care Products, and Perfluorinated Alkyl Substances in Water Treatment

Abstract: This investigation presents a method of simultaneous pharmaceuticals and personal care product (PPCP) and perfluorinated alkyl substance (PFAS) removal utilizing zeolite–sodium silicate composite materials. Sorption efficacy of five synthetic zeolite composites and one natural zeolite was tested through batch experimentation using two aqueous matrices: (1) a lab-controlled mixture of 21 PPCPs and PFASs and (2) wastewater treatment facility (WWTF) effluent samples collected from three locations and analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similarly, on a surface-area-normalized basis, silica sand had the highest sorptive capacity for PFOS compared to goethite, kaolinite, or iron-enriched sand . Others have also observed preferential sorption of PFAS to siliceous zeolite compounds in the absence of OC. , Accordingly, we reject the assumption that organic carbon content can be used as a single predictor variable for PFAS M R (assumption 1).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, on a surface-area-normalized basis, silica sand had the highest sorptive capacity for PFOS compared to goethite, kaolinite, or iron-enriched sand . Others have also observed preferential sorption of PFAS to siliceous zeolite compounds in the absence of OC. , Accordingly, we reject the assumption that organic carbon content can be used as a single predictor variable for PFAS M R (assumption 1).…”
Section: Resultsmentioning
confidence: 64%
“…55 Others have also observed preferential sorption of PFAS to siliceous zeolite compounds in the absence of OC. 79,80 Accordingly, we reject the assumption that organic carbon content can be used as a single predictor variable for PFAS M R (assumption 1). S12 and S7, respectively) and eventually yielded the following model )) (eq 3) (r 2 = 0.84, p < 0.001).…”
Section: Retention Of Molecular Cohorts Of Pfas As a Function Of Equi...mentioning
confidence: 99%
“…More research is required to elucidate the rate-determining mechanisms for different PFAAs on CDP granules of different sizes and in the presence of more complex matrix constituents. The challenges encountered and described in this research are broadly relevant as more types of novel adsorbents are being discovered to address PFASs and other emerging contaminants, , and more techniques to develop defined morphology of novel adsorbents are being explored. …”
Section: Discussionmentioning
confidence: 99%
“…Wanzek et al demonstrated PFAS adsorption onto saturated soils after only a single application of AFFF at concentrations 1000 times below the mixture’s CMC. Anionic PFAS sorption was attributed to the strong hydrophobicity and exclusion from the aqueous phase and was only poorly correlated with electrostatic attraction to oxalate extractable iron (Fe ox ) and organic carbon (%OC), which is supported in the literature. , The sorbent parameters, Fe ox and %OC, were statistically related to the number of nitrogen atoms found in zwitterionic PFAS molecules that possess both positive and negative charges, providing a mechanistic understanding of these structural PFAS features to interactions with charged soil surfaces. ,, Wanzek et al also presented a polyparameter quantitative structure–property relationship (ppQSPR) of PFAS retention in saturated soils of AFFF-impacted source zones for concentrations below CMC. However, the model was developed using AFFF concentrations below CMC and employed a single application of AFFF that would not reveal the potential effect of surfactant–surfactant interactions on PFAS retention.…”
Section: Introductionmentioning
confidence: 75%